Reference Architecture for the Telecommunications Industry : Transformation of Strategy, Organization, Processes, Data, and Applications /: Transformation of Strategy, Organization, Processes, Data, and Applications. (2017) - Czarnecki, Christian; Dietze, Christian
No abstract available